PSVI-10 Preliminary Evaluation of Small Ruminant Production Systems in Mississippi and the Southern US. (21st September 2022) - Dearborn, Lindsey; de Alvarez, Leyla Rios; Lemus, Rocky; Downey, Laura; Rico-Mendez, Gina; Maples, Joshua; Pesato, Michael; Graves, Jessica
Abstract: An online survey was used to collect farmer-level data about farm characteristics, number of animals and species, and farmer socio-demographic information, to evaluate small ruminant production systems in Mississippi (MS) and the Southern USA. Survey data was collected from July 2021 to March 2022 (IRB-21-202), with 243 participants, using the support of MS Sheep and Goat Associations, and MS State University social media. Responses include farmers located in MS (66.3%), TN (9.8%), AL (6.3%), NC (3.4%), KY (2.9%), FL (2%), GA (2%), LA (2%), OK (2%), TX (2%), AR (1%), and VA (0.5%). Respondents were 53.1% females and 46% males with an average age of 45 and 48.9 years, respectively. Ethnic distribution was 96.5% non-Hispanics and 2.5% Hispanics. Race distribution was 90.2% White, 2.9% African American, 2.9% American Indian/Alaska Native, and 0.5% Asian. Educational level was 25.9% Bachelor, 24.4% Associate, 21.5% High School, and 20.5% Postgraduate. Farming experience was 30.7% (0 to 5 yr), 23.4% (6 to 10 yr), 20.5% (11 to 20 yr), 10.2% (21 to30 yr), 9.3% (31 to 40 yr), and 5.9% (> 40 yr). Livestock present among farms was 70% goats, 29.6% beef, 24.7% sheep, 23.4% horses, and 4.1% dairy cattle. They indicated that 44.6% had 26 to 100 animals, 27.2% had 11 to 25, 16.8% had <10 sheep/goats, 5.4% 101-150, 3.5% 151-20, and 2.5% >250. Farm size in the 39% ranged from 21 to 100 ac, 24.9% < 10 ac, 18% from 11 to 20 ac, and 18% >100 ac. These results differ from USDA (2021) by suggesting that sheep and goat producers in the Southern US are predominantly middle-aged individuals, with medium to large size farms, and low number of years of experience in farming. These findings will be used to develop future outreach and educational programs that could help producers increase production efficiency.